Pengaruh Pengalaman Kerja, Disiplin, Kompensasi dan Motivasi Terhadap Kinerja Pegawai RSUD Rantauprapat - Sukma, Melati; Broto, Bayu Eko; Hendry, Raja Saul Marto (Journal of Computer Science and Information System(JCoInS), 2024)
This study aimed to determine the effect of work experience, discipline, Work, Compensation, and motivation on employee performance in regional public hospitals Rantauprapat. Samples in this study were employees of the Regional General Hospital with a total of 90 rantauptapat. From the research, there is a positive and significant effect of work experience variables on performance with t count X1 equal to 4.571 smaller than T table equal to 1.67 with significance 0.000<0.05, there is a positive but not significant effect of work discipline variables on Employee Performance With t count X1 equal to 0.090 smaller than T table 1.67 and significance 0.242 > 0.05, there is 1.67 and significance 0.132>0.05, there is a positive and significant effect of motivation on Employee Performance With t count X 2 of 4.271 greater than T table of 1.96 and significance of 0.000 < 0.05, there is a simultaneous influence of independent variables work experience, work discipline, compensation and motivation on performance shows F count of 30.549 greater than F table of 2, 60 with significance of 0.000< 0.005.